A novel path to runaway electron mitigation via deuterium injection and current-driven MHD instability. (14th October 2021) - Paz-Soldan, C.; Reux, C.; Aleynikova, K.; Aleynikov, P.; Bandaru, V.; Beidler, M.; Eidietis, N.; Liu, Y.Q.; Liu, C.; Lvovskiy, A.; Silburn, S.; Bardoczi, L.; et al.
Abstract: Relativistic electron (RE) beams at high current density (low safety factor, q a ) yet very low free-electron density accessed with D2 secondary injection in the DIII-D and JET tokamak are found to exhibit large-scale MHD instabilities that benignly terminate the RE beam. In JET, this technique has enabled termination of MA-level RE currents without measurable first-wall heating. This scenario thus offers an unexpected alternate pathway to achieve RE mitigation without collisional dissipation. Benign termination is explained by two synergistic effects. First, during the MHD-driven RE loss events both experiment and MHD orbit-loss modeling supports a significant increase in the wetted area of the RE loss. Second, as previously identified at JET and DIII-D, the fast kink loss timescale precludes RE beam regeneration and the resulting dangerous conversion of magnetic to RE kinetic energy. During the termination, the RE kinetic energy is lost to the wall, but the current fully transfers to the cold bulk thus enabling benign Ohmic dissipation of the magnetic energy on longer timescales via a conventional current quench. Hydrogenic (D2 ) secondary injection is found to be the only injected species that enables access to the benign termination. D2 injection: (1) facilitates access to low q a in existing devices (via reduced collisionality & resistivity), (2) minimizes the RE avalanche by 'purging' the high-Z atoms from the RE beam, (3) drives recombination of the background plasma, reducing the density and Alfven time, thus accelerating the MHD growth. This phenomenon is found to be accessible when crossing the low q a stability boundary with rising current, falling toroidal field, or contracting minor radius—the latter being the expected scenario for vertically unstable RE beams in ITER. While unexpected, this path scales favorably to fusion-grade tokamaks and offers a novel RE mitigation scenario in principle accessible with the day-one disruption mitigation system of ITER.